Management of central nervous system demyelinating diseases during the coronavirus disease 2019 pandemic: a practical approach - Apóstolos, Samira Luisa Pereira (2020)
Background: The novel coronavirus disease 2019 (COVID-19) pandemic poses a potential threat to patients with autoimmune disorders, including multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD). Such patients are usually treated with immunomodulatory or immunosuppressive agents, which may tamper with the organism’s normal response to infections. Currently, no consensus has been reached on how to manage MS and NMOSD patients during the pandemic. Objective: To discuss strategies to manage those patients. Methods: We focus on how to 1) reduce COVID-19 infection risk, such as social distancing, telemedicine, and wider interval between laboratory testing/imaging; 2) manage relapses, such as avoiding treatment of mild relapse and using oral steroids; 3) manage disease-modifying therapies, such as preference for drugs associated with lower infection risk (interferons, glatiramer, teriflunomide, and natalizumab) and extended-interval dosing of natalizumab, when safe; 4) individualize the chosen MS induction-therapy (anti-CD20 monoclonal antibodies, alemtuzumab, and cladribine); 5) manage NMOSD preventive therapies, including initial therapy selection and current treatment maintenance; 6) manage MS/NMOSD patients infected with COVID-19. Conclusions: In the future, real-world case series of MS/NMOSD patients infected with COVID-19 will help us define the best management strategies. For the time being, we rely on expert experience and guidance.